Cytochemical and molecular properties of simian virus 40 transformed Kaposi's sarcoma-derived cells: evidence for the secretion of a member of the fibroblast growth factor family. - Werner, Sabine; Hofschneider, Peter Hans; Stürzl, Michael; Dick, Irene; Roth, Willi Kurt (Journal of Cellular Physiology, 1989)
Contact-inhibited Kaposi's sarcoma-derived cells (KS cells) were transfected with Simian Virus 40 (SV40) DNA. Transformed cells (SV-KSC) were selected for their capacity to form foci on monolayers of the low-malignant KS cells. Isolated SV-KSC foci were found to contain integrated SV40 DNA sequences and to express SV40 large T-antigen. Several differentiation properties of KS cells are retained in the SV40 transformants, e.g., expression of vimentin and the endothelial cell marker BMA 120. In contrast to the maternal KS cells, SV-KSC are capable of growing in platelet-derived growth factor (PDGF)-depleted platelet-poor-plasma serum (PPPS) and in soft agar. However, they are not tumorigenic in nude mice. Expression of the oncogenes c-myc, c-N-ras, c-Ha-ras, and p53 is significantly elevated in SV-KSC, whereas c-fos and c-erb B expression is comparable to that of KS cells and fibroblasts. Conditioned medium from SV-KSC can substitute for PDGF when PDGF-dependent, nontransformed KS cells are grown in PPPS. Biochemical analysis of the SV-KSC supernatant and PDGF A and B mRNA expression analysis provide evidence that the mitogenic activity is not due to a PDGF-like growth factor. On the other hand, there is evidence to indicate that the SV-KSC mitogen is a member of the fibroblast growth factor family. SV-KSC represent an interesting model system for the study of different degrees of malignancy of cultured mesenchymal cells and especially provide an important source for the isolation of a potent growth factor for KS cells and other mesenchymal cells in vitro.